Performance Study of a Humpback Whale Fluke Turbine on Foil Shape Variation Based on Double Multiple Streamtube Model - Ariefianto, Rizki Mendung; Hasanah, Rini Nur; Wijono, Wijono; Ridlwan, Asfarur (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2023)
Exploration of ocean current energy allows for the development of turbines as the primary conversion device. Turbine technologies have been developed in various types, including bio-inspired turbines, such as the humpback whale fluke turbine. In this study, the achievement of a humpback whale fluke turbine is investigated by applying various forms of foil, both symmetric and asymmetric, to obtain the appropriate foil profile. Symmetric foils were represented by NACA 0012, NACA 0018, and NACA 0021, while asymmetric foils were represented by NACA 4312, NACA 4512, and NACA 4712 foils. Simulations were performed using QBlade software, which was developed based on the DMST theory. In general, symmetric foils have a more stable performance than asymmetric foils because they produce a better performance at positive and negative angles of attack. This result is also supported by a review of efficiency and self-starting capability where symmetric foils have significantly higher CP values and positive CQ along the azimuth angle than asymmetric foils. Finally, NACA 0021 foil is recommended for a humpback whale fluke turbine based on its efficiency and self-starting capability.